By-Laws - Jamaica Association of Montreal (JAM) (2021)

Semaji - Black Community Resource Centre (BCRC) (2021)

Semaji - Black Community Resource Centre (BCRC) (2021)

Semaji - Black Community Resource Centre (BCRC) (2021)

Black in Quebec Presents : In Focus - Davids, John; Fang, Xiaoyan (Black Community Resource Centre (BCRC), 2021)
Due to the Information Gaps pertaining to the well-being of the ESBC, the project collected detailed, qualitative information from members of Quebec's ESBC through conducting Focus Groups. These were meant to better inform the project about different aspects of the community such as the challenges facing the ESBC and solutions which should be considered. This process occurred in two parts, one-on-one interviews with members of the ESBC as well as group discussions with members of the seniors in the ESBC. Ultimately, upon conducting the Focus Groups, the Black in Quebec team was provided with a large amount of detailed, qualitative data derived directly from community members. This document presents the findings from the Focus Groups which are organized in two parts: challenges identified and solution based responses. Given that the Focus Group discussions were semistructured and participants offered varying levels of details, the findings reflect distinct issues or solutions identified by the participants in no particular order but were categorized thematically. Certain findings may have overlapped more than one theme.

Quebec's English-speaking Black Community : An Analysis of the Outcomes and Information Gaps - Black Community Resource Centre (BCRC) (2021)
Black in Quebec (BIQ) is a research project being undertaken by the Black Community Resource Center (BCRC), a non-profit organization founded in 1995, which serves Montreal’s English-speaking Black Community (ESBC) by providing individuals with services and information that they need. The BIQ project seeks to answer the Research Question: What is the relative well-being of the English-speaking Black community in Quebec? The relatively unique positioning of the ESBC in the Quebec landscape, being both a visible minority and linguistic minority group, necessitates that research be conducted to further understanding of the experiences and situations facing this community, which are particular to the group or shared more widely across society. The overall vision of this project is to consolidate the collection and dissemination of data that pertains to Quebec’s English-speaking Black community and share this information across a variety of institutions, including Black community organizations, public institutions, and social research groups.

Semaji - Black Community Resource Centre (BCRC) (2021)

Semaji - Black Community Resource Centre (BCRC) (2021)

Semaji - Black Community Resource Centre (BCRC) (2021)

Did the Black Lives Matter Movement Help English-speaking Black Young Adults in Quebec Recover from the Damaging Psychological Effects of the COVID-19 Pandemic? - Koestner, Richard; Holding, Anne C. (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
The historic events of the spring of 2020—the collision of the worst public health crisis in a century and the largest Black civil rights movement in half a century—offer a unique opportunity to examine how the frustrations and hopes of English-speaking Black young adults were affected. We sought to understand the potentially competing impacts that the public health and social justice crises have had on the young adults in their communities. Quebec has the second largest Black population in Canada (after Ontario), with 27% of Canada’s total Black population. Quebec’s Black population has doubled in size in the past 20 years, with 325,000 people currently living here. This population is predominantly French speaking (80%), and it is concentrated in the Montreal metropolitan area (over 90%). The Black population tends to be younger than the Canadian average, and its members are more likely to be first-generation Canadians.

Semaji - Black Community Resource Centre (BCRC) (2021)

2021 Community Vitality Survey : Black in Quebec - Black Community Resource Centre (BCRC) (2021)
This report offers a comprehensive overview of the 2021 Community Vitality Survey which was conducted by the Black in Quebec project team. Black in Quebec was launched in Fall 2019 and was a research project by the Black Community Resource Centre (BCRC) which researched the well-being and vitality of Quebec's English-speaking Black Community (ESBC). This is the third report to be released by the project team and complements the two previous research based publications. The first published report was Quebec's English-speaking Black Community: An Analysis of Outcomes and Information Gaps which was based on an assessment of currently available information pertaining to the English-speaking Black Community in Quebec. The second report to be released was entitled Black in Quebec presents: In Focus and it presented an overview of the Focus Groups conducted by the project team from May to December of 2020. This report focuses exclusively on the 2021 Community Vitality Survey which was conducted from April to June 2021 and provides a detailed overview of the survey. It is the last research based report to be released by the Black in Quebec project before the release of a final, comprehensive project summary report.

Black in Quebec : Summary Report 2020-2021 - Black Community Resource Centre (BCRC) (2021)
In Quebec, there is a population of around 320,000 people who identify as members of the Black community. In Quebec's Black community, just under 60,000 (around 1 in 5 people) are categorized as members of the English-speaking community (Statistics Canada, 2016). The Black in Quebec Project commenced in Fall 2019 with the drafting of the project and in February 2020, the Project Researcher (John Davids) and Research Assistant (Xiaoyan Fang) were hired by the BCRC. The purpose of the project is to fill the gaps in the knowledge about the English-speaking Black Community (ESBC) in Quebec. In Quebec and Canada, there is a lack of disaggregated race-base data that measures critical variables describing the socio-economic and psycho-social status of the English-speaking Black Community. Thus, when it came to exploring the state and vitality of the ESBC, there were and continues to be deficiencies in the publicly available data and knowledge. Being a study about a population that is both a racialized and linguistic minority in Quebec, the Black in Quebec Project attempts to fill some of the gaps in the collection of data, its analysis and storage. It presents an improved understanding regarding the unique situation and challenges facing the ESBC in Quebec.

Black in Quebec - Davids, John; Fang, Xiaoyan; Bramble, Shania (2021)

Activity Report 2020-2021 - Jamaica Association of Montreal (JAM) (2021)
The Association was founded in November 1962, shortly after Jamaica’s Independence in August 1962. Our seal of Incorporation was granted in 1970. Since its inception, the Association has grown strong in attracting members. It is recognized as the official organization representing Jamaicans in Montreal at the Federal, Provincial and Municipal levels. We have accompanied delegations and presented briefs to all levels of government. Given our commitment to community development, the Jamaica Association developed our Mission Statement as follows: “To assist in improving and enhancing the quality of life for the Jamaican Community”.